Analysing Errors Made by Kurdish EFL Learners in Applying the Rules of Syntactic Structure - Ahmed, Hazhar Ramadhan (Journal of Educational and Psychological Sciences, 2020)
This paper intended to investigate and analyse errors by Kurdish EFL learners in applying the rules of syntactic structure. The paper adopted a descriptive-analytical method for data collection and analysis, so a purposive sample of 20 Male students at University Level in the Kurdistan region. The researcher conducted a test consisted of two questions, after that, the responses were statistically treated and analysed. This analysis has shown very important results that were used for the discussion. Finally, the paper concluded findings, also the students of the English Language at Universities have the same problem, however, some of them can learn English and they can speak very well, but they haven't enough grammatical and syntactical ability towards the English Language as a Foreign Language, and researcher recommended that teachers have to give enough information about rules of syntactic structure, and students should do more practice when they applying analysis of rules.
Keywords: Errors; Kurdish EFL; Learners; Syntactic Structure; EFL